The Effect of Religiosity, Demography, and Motivation on Student Sharing Behavior Patterns - Febrianto, Nur Fitroh; Arilia, Linawati; Rahmawati, Fadhilah; Muharromah, Gabriele Lailatul; Ridlwan, Ahmad Ajib (http://jagadalimussirry.com/, 2019)
Provision of donations in Indonesia has increasingly experienced significant development. Thepurpose of this study was to determine how the influence of religiosity, demographic, and motivation levelvariables of Surabaya State University Economics Faculty students on patterns of sharing behavior. Based onthese results it can be concluded that the Faculty of Economics students do sharing behavior because it isinfluenced by demographic factors and motivation not because of the factor of religiosity, so that the higher orlower levels of student religiosity do not determine the amount of sharing made by students.